The effectiveness of product strategies in positioning Perodua Sdn Bhd as preffered brand among car purchasers / Nuraini Mohd Yusof - Mohd Yusof, Nuraini (Faculty of Business and Management, 2008)
We have many automotive companies registered in Malaysia with a variety of their product lines. Thus, car purchasers in Malaysia will have a lot of choices. Cars are necessity for Malaysian people because their obligation in life such as going to work and many more. To cope with this scenario, Perodua must focus on providing products from a demand side perspective. This research is about a study on the effectiveness of Perodua's product strategies in positioning its brand as preferred brand among car purchasers. The methodology used for this research is convenience sampling whereby 100 people who owned Perodua cars at Bukit Sentosa Rawang are currently picked. The collected the data were analyzed and summarized in a readable and easily interpretable form. From the final analysis, monthly income and occupation have significant difference towards product strategies. In this study, the researcher can conclude that the higher is the income and the more the occupation of the respondents categorized as professionals, the least will be the respondents' buying Perodua car. In other hand, all the independent variables i.e. consumer motivation, personality and consumer behavior, consumer perception, consumer learning and attitude formation have relationship with product strategies. It can be concluded based on the relationship that the consumers' perception is highly influence the product strategies. Thus Perodua car purchasers highly preferred a car with good design.